Afua Kuma’s Prayers and Praises as Evidence of a Vibrant Primal Substructure in African Christianity - Joseph Awuah Gyebi (E-Journal of Religious and Theological Studies, 2021)
Following from the assertion that there exists a symbiosis between Christianity and the Primal Substructure in Africa, this paper sets out to examine Afua Kuma’s Jesus of the Deep Forest using Harold Turner’s six feature analysis of primal religions. It focuses on how Afua Kuma’s poetry builds upon the six features of the primal worldview with her new insights from the Christian faith. The author argues that this is evidence of the vibrant primal substructure in African Christianity. This article thus contributes to the growing body of scholarship on African Christianity and its primal underpinnings and Christianity as a non-Western religion